2023
DOI: 10.1093/jambio/lxad166
|View full text |Cite
|
Sign up to set email alerts
|

Fate of microbial contamination in a South European Coastal Lagoon (Ria Formosa) under the influence of treated effluents dispersal

Abstract: Aim Assessment of the fate of microbial contamination driven from treated wastewater disposal at a highly productive zone on a South European coastal lagoon (Ria Formosa). Methods and results Microbial indicators of contamination (Total coliforms, Escherichia coli and Enterococci) were evaluated monthly during September 2018-September 2020, at three study areas (Faro, Olhão, Tavira) under different wastewater discharge flows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
0
0
Order By: Relevance
“…The relatively restricted hydrodynamics over the two innermost stations [48], together with sampling during neap low tides (see [30]), can explain this water quality gradient. The distribution of the microbial indicators of faecal contamination assessed concurrently with our study also showed a reduction along the 1.5 km longitudinal transect, with a strong dilution effect during high tide [118]. However, regardless of the WWTP influence, increased agricultural nutrient runoff, confinement, shallowness, sediment resuspension, and biological activity could partially justify the higher nutrient concentrations in the inner compared to outer coastal lagoon areas (e.g., [42,46]).…”
Section: Abiotic Environmental Settingsupporting
confidence: 60%
“…The relatively restricted hydrodynamics over the two innermost stations [48], together with sampling during neap low tides (see [30]), can explain this water quality gradient. The distribution of the microbial indicators of faecal contamination assessed concurrently with our study also showed a reduction along the 1.5 km longitudinal transect, with a strong dilution effect during high tide [118]. However, regardless of the WWTP influence, increased agricultural nutrient runoff, confinement, shallowness, sediment resuspension, and biological activity could partially justify the higher nutrient concentrations in the inner compared to outer coastal lagoon areas (e.g., [42,46]).…”
Section: Abiotic Environmental Settingsupporting
confidence: 60%